1998
DOI: 10.1152/ajpheart.1998.274.3.h883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tumor necrosis factor-α and interleukin-1α on heme oxygenase-1 expression in human endothelial cells

Abstract: Heme iron exacerbates oxidant damage by catalyzing the production of free radicals. Heme oxygenase is the rate-limiting enzyme involved in heme catabolism. An inducible form of heme oxygenase, heme oxygenase-1 (HO-1), is upregulated in oxidant and inflammatory settings, and recent work suggests that HO-1 induction may serve a protective function against oxidant injury. The ability of the endogenous inflammatory mediators, interleukin (IL)-1α, tumor necrosis factor-α (TNF-α), and IL-6, to enhance HO-1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 61 publications
5
114
2
Order By: Relevance
“…This native response is likely caused by I͞R-mediated activation of the inflammatory cascade and the consequent release of cytokines. Indeed, cytokines have been reported to induce HO-1 expression both at the transcriptional and posttranscriptional levels (32). Despite HO-1 protein levels that equaled or surpassed those in the hHO-1-treated rats, this ''late'' response was clearly not enough to provide significant myocardial protection in the lacZ-treated animals.…”
Section: Discussionmentioning
confidence: 98%
“…This native response is likely caused by I͞R-mediated activation of the inflammatory cascade and the consequent release of cytokines. Indeed, cytokines have been reported to induce HO-1 expression both at the transcriptional and posttranscriptional levels (32). Despite HO-1 protein levels that equaled or surpassed those in the hHO-1-treated rats, this ''late'' response was clearly not enough to provide significant myocardial protection in the lacZ-treated animals.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors have shown that HO-1 was induced by heat shock, heavy metals, hypoxia and endotoxin (Eyssen-Hernandez et al 1996, Carraway et al 1998, Panchenko et al 2000, Stuhlmeier 2000. Furthermore, HO-1 was induced by TNF- (Terry et al 1998), which is known to stimulate granulosa cell apoptosis (Kaipai et al 1996). In porcine granulosa cells, we have demonstrated that HO-1 was mainly expressed in granulosa cells in the atretic follicle, and was present in freshly isolated and cultured granulosa cells, but we have not studied the nature of the factors that induced HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…NF-E2-related factor 2 (Nrf2) is an important transcription factor that regulates expression of antioxidant defense genes through binding to antioxidant response elements in the promoter region, such as HO-1. 14 HO-1 has been reported to play a critical role in protection against oxidative tissue injury following ischemia and inflammation, 15 however, the mechanism is not clear. Therefore, we determined the role of HO-1 in TNF-␣-mediated adhesion molecules expression and airway inflammation in vitro and in vivo.…”
Section: The P47mentioning
confidence: 99%